2000
DOI: 10.1097/00000658-200012000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Complications and Death After Pancreaticoduodenectomy: Risk Factors and the Impact of Hospital Volume

Abstract: ObjectiveTo perform a two-part study of pancreaticoduodenectomy in the Netherlands, focusing on the effects of risk factors on outcomes in a single high-volume hospital and the effect of hospital volume on outcomes. Summary Background DataHospital volume and surgeon caseload can be related to the rates of complications and death, and the influence of risk factors can be volume-dependent. Provision of regionalized care should take this into account. MethodsIn part A, a single-institution database on 300 consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

30
505
4
33

Year Published

2002
2002
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 774 publications
(572 citation statements)
references
References 28 publications
30
505
4
33
Order By: Relevance
“…Several studies (Edge et al, 1993;Gordon et al, 1995;Lieberman et al, 1995;Neoptolemos et al, 1997;Gouma et al, 2000;Garden, 2001;NHS Executive, 2001;Rosemurgy et al, 2001;Teisberg et al, 2001;Birkmeyer et al, 2002;Halm et al, 2002;Bachmann et al, 2003) have suggested that specialisation in this field may yield better results in terms of postoperative mortality, surgical complications, and longer term survival, although other studies have not found this relationship (Wade et al, , 1996, and the possibility of publication bias must be considered. Some previous studies are subject to the criticism that in-hospital mortality was used as an outcome, despite the fact that length of stay may be lower in patients treated by specialist pancreatic surgeons or hospitals with higher caseloads (Imperato et al, 1996;Sosa et al, 1998;Gordon et al, 1999;Simunovic et al, 1999;Rosemurgy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (Edge et al, 1993;Gordon et al, 1995;Lieberman et al, 1995;Neoptolemos et al, 1997;Gouma et al, 2000;Garden, 2001;NHS Executive, 2001;Rosemurgy et al, 2001;Teisberg et al, 2001;Birkmeyer et al, 2002;Halm et al, 2002;Bachmann et al, 2003) have suggested that specialisation in this field may yield better results in terms of postoperative mortality, surgical complications, and longer term survival, although other studies have not found this relationship (Wade et al, , 1996, and the possibility of publication bias must be considered. Some previous studies are subject to the criticism that in-hospital mortality was used as an outcome, despite the fact that length of stay may be lower in patients treated by specialist pancreatic surgeons or hospitals with higher caseloads (Imperato et al, 1996;Sosa et al, 1998;Gordon et al, 1999;Simunovic et al, 1999;Rosemurgy et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has recently been suggested that there may be some scope for improvement in survival figures in the UK (NHS Executive, 2001;Garden, 2001). This guarded optimism is based on accumulating evidence that the concentration of treatment activity among fewer high volume hospitals and/ or surgeons (as a proxy for specialisation) may lead to improved outcomes for patients with pancreatic cancer (Edge et al, 1993;Gordon et al, 1995;Lieberman et al, 1995;Neoptolemos et al, 1997;Gouma et al, 2000;NHS Executive, 2001;Garden, 2001;Rosemurgy et al, 2001;Teisberg et al, 2001;Halm et al, 2002;Birkmeyer et al, 2002;Bachmann et al, 2003). Many of the studies report reduced postoperative morbidity and mortality rates, and shorter postoperative hospital stays following resection of pancreatic cancer, although few have analysed long-term outcome.…”
mentioning
confidence: 99%
“…Pancreaticoduodenectomy for pancreatic cancer or radical oesophagectomy for oesophageal cancer are more surgically aggressive procedures than D2 gastrectomy and are recommended to be performed exclusively in specialised centres. They do not carry a risk of hospital mortality of over 10% in such centres (Altorki and Skinner, 1997;Gordon et al, 1998;Bottger and Junginger, 1999;Lerut et al, 1999;Tsiotos et al, 1999;Gouma et al, 2000;Karl et al, 2000). Postoperative mortality of over 10% is no longer acceptable in any kind of cancer surgery.…”
Section: Survival Of Igcsg D2 Gastrectomy Phase II Study M Degiuli Et Almentioning
confidence: 99%
“…The operation classically involves removal of the pylorus and antrum; however recently, surgeons have used a pylorus-preserving Whipple procedure to lower the incidence of postgastrectomy symptoms, such as delayed gastric emptying. Both methods -the standard and the pylorus-preserving Whipple-have their advocates, but each method continues to have gastroparesis as a postoperative problem [4,10,[20][21]. In our study, 11 (8.7%) of 126 patients underwent PD complicated delayed gastric emptying after operation.…”
Section: Discussionmentioning
confidence: 72%
“…A recent study from Yeh et al [18], identified jaundice, creatinine clearance abnormality, and intraoperative blood loss as significant risk factors for leakage. Matsusue et al [19], found that One of the most common morbidities after PD is delayed gastric emptying with rates of 15-40% [20][21]. Advances in surgical skills and postoperative care have resulted in mortality rates of <5% [22][23].…”
Section: Discussionmentioning
confidence: 99%